Topology optimization of the periodic pile barrier with initial stresses arranged in rectangular and equilateral triangular lattices. (May 2023) - Zhou, Peng; Wan, Shui; Wang, Xiao; Fu, Jundong; Li, Shuli
Abstract: The attenuation zones (AZs) of periodic pile barriers can be used to suppress ambient vibration in specific frequency ranges. Topology optimization of periodic pile units can search for efficient pile structures. However, in the process of optimization, the influence of initial stresses on the AZs is usually ignored, and the periodic piles are often arranged in a square lattice. In this paper, to maximize the relative width of AZs (RWAZs), the genetic algorithm (GA) and nondominated sorting genetic algorithm-II (NSGA-II) are adopted for single- and multiobjective topology optimization of the periodic pile unit with different initial stresses. Periodic piles arranged in rectangular lattices with different aspect ratios and those in an equilateral triangular lattice are considered, and the corresponding optimized pile structures are obtained. It is found that with the same unit area, the periodic piles with the equilateral triangular layout correspond to the largest RWAZ. Due to the existence of the initial stress, the position and width of the AZs of the optimized pile structure decrease. The RWAZ of the optimized pile structure decreases with increasing initial stresses. Finally, numerical results from both frequency domain and time domain analyses demonstrate that the optimized pile barrier can effectively isolate elastic waves, which shows extensive application prospects in engineering practice.